O Parnaso Lusitano e a formação do cânone : a invenção do arcadismo na historiografia da literatura brasileira (1757-1827) - Pacheco, Mirela Magnani (2011)
The present work investigates the relevance of the Parnaso Lusitano (1826), written by the portuguese author, named Almeida Garrett (1799-1854), in the construction process of the first Brazilian literary canon, proposing an analysis of the way his critique has been (re) appropriated by other eighteenth century literary anthologies, as well as the Brazilian literary historiography, serving as theorical basis for the scholar use of this literature, and contributing to the invention of the Arcadianism in its historiography. Thus, aiming at the objectives presented, besides the legislation related to literature teaching in each period, some eighteenth century anthologies, florilegiums, as well as other anthologic writings published between 1830 and 1860 various theoretical sources have been used as a reference, such as: literary theory (WILLIAMS, 1958; EAGLETON, 1983; CULLER, 1999; BLOOM, 1994; KHOTE, 1997), literary history (CARPEAUX, 1959; CÉSAR, 1978; ROUANET, 1991; SOUZA, 1999, 2007; ABREU, 2003; TEIXEIRA, 1999; WEBER, 1997; ZILBERMAN, 1994, 1997; ZILBERMAN e MOREIRA, 1998); cultural history (ANDERSON, 2008; RENAN, 2008; HALL, 2005;) and history of school subjetcs (CHERVEL, 1990; HÉBRARD, 1999; OLIVEIRA, 2004, 2008, 2010).